The Role of Rac-1 Inhibitor in Management of Acute Pancreatitis and Regulation of Chemokine in rat’s model - Othman, Farman Naseh; Nanakali, Nadir Mustafa (Journal of Neonatal Surgery, 2025)
Background: Acute pancreatitis is a common inflammatory disease of the exocrine pancreas, characterized by a mortality rate ranging from 1% to 5%. This condition has the potential to lead to organ dysfunction, pancreatic necrosis, and subsequent organ failure. Aim: Rac1, a G-protein with a molecular weight of approximately 21 kD, has been demonstrated to govern various platelet functions. We hypothesized that the inhibition of Rac-1 signaling could be implicated in severe acute pancreatitis (AP). Our study aimed to explore the impact of a Rac- 1 inhibitor on decrease of lipase enzyme and chemokine (IL-6 and CXCL1), and its potential in safeguarding against tissue damage associated with severe acute pancreatitis. Method: In this experimental study, male albino rats were employed, and the rats received pretreatment with a specific Rac1 inhibitor, NSC23766, at a dosage of 5 mg/kg. Subsequently, a midline laparotomy was performed on the anesthetized animals, followed by L-arginine injection intra-peritoneally. Blood Lipase levels were measured, and the concentration of serum chemokines (IL6 and CXCL1) were assessed using ELISA. Additionally, leukocyte counting, and histopathological examination were conducted to analyze morphological changes in the pancreas. Results: The blood lipase levels were notably elevated in rats with acute pancreatitis compared to the control rats. Our findings indicated that acute pancreatitis was induced in rats through L-arginine injection. Rac1 expression was upregulated in rats with acute pancreatitis, and pre-treatment with Rac-1 led to a non-significant decrease in lipase levels compared to the acute pancreatitis group. Furthermore, the levels of IL6 and CXCL1 were higher in acute pancreatitis group compared to the control group. Conclusion: Our investigation underscores the pivotal role of Rac-1 in regulating lipase activity during severe acute pancreatitis (AP). Additionally, it highlights the involvement of Rac-1 in platelet activation and the secretion of chemokines, namely IL6 and CXCL1, attributed to inflammation in organ tissues during acute pancreatitis. Targeting Rac1 emerges as a promising and innovative approach for the treatment of severe acute pancreatitis, offering potential control over inflammation and tissue damage